Proteomic Analysis of MCF-7 Breast Cancer Cell Line Exposed To Leptin - A. Valle; J. Sastre-Serra; C. Pol; A. M. Miró; J. Oliver; P. Roca (Analytical Cellular Pathology)
Background: Obesity is a well-known factor risk for breast cancer in postmenopausal women. Circulating leptin levels are increased in obese and it has been suggested to play an important role in mammary tumor formation and progression. To contribute to the understanding of the molecular mechanisms underlying leptin action in breast cancer, our aim was to identify proteins regulated by leptin in MCF-7 human breast cancer cells. Methods: We used two-dimensional gel electrophoresis (2-DE) and matrix assisted laser desorption/ionization time of flight mass spectrometry (MALDI-TOF MS) to identify proteins affected by leptin. Results: Thirty proteins were found differentially expressed in MCF-7 cells after 48 h leptin exposure. Proteins regulated by leptin included proteins previously implicated in breast cancer such as catechol-o-methyltransferase, cathepsin D, hsp27, serine/threonine-protein phosphatase and regulatory proteins of the Ras signaling pathway. Proteins involved in other cellular functions such as stress response, cytosqueleton remodeling and proteins belonging to ubiquitin-proteasome system, were also identified. Furthermore, leptin-treated cells showed a substantial uptake of the serum carrier proteins albumin and alpha-2-HS-glycoprotein. Conclusions: This screening reveals that leptin influences the levels of key proteins involved in breast cancer which opens new avenues for the study of the molecular mechanisms linking obesity to breast cancer.